2014
DOI: 10.1016/j.ajpath.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Activation Is Reactive Oxygen Species Dependent and Mediates Irinotecan-Induced Mucositis through IL-1β and IL-18 in Mice

Abstract: Irinotecan is a useful chemotherapeutic for the treatment of various cancers. Irinotecan treatment is associated with mucositis, which clearly limits the use of the drug. Mechanisms that account for mucositis are only partially known. This study assessed mechanisms and the role of inflammasome activation in irinotecan-induced mucositis. Mucositis in mice was induced by irinotecan injection in C57BL/6 wild-type, gp91phox(-/-), il-18(-/-), casp-1(-/-), and asc(-/-) mice once a day for 4 consecutive days. In some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 52 publications
(35 reference statements)
3
50
0
Order By: Relevance
“…It was recently reported that mitochondrial ROS may promote inflammation by activating the multiprotein cytoplasmic complexes inflammasome NLRP3 [34,35]. NLRP3 inflammasome activation leads to caspase-1 activation and subsequent cleavage of pro-cytokines, such as IL-1β, into their mature forms.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that mitochondrial ROS may promote inflammation by activating the multiprotein cytoplasmic complexes inflammasome NLRP3 [34,35]. NLRP3 inflammasome activation leads to caspase-1 activation and subsequent cleavage of pro-cytokines, such as IL-1β, into their mature forms.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that ROS-activated inflammasome increases intestinal mucositis in mice treated with chemotherapeutic agent, irinotecan [37]. Administration of IL-1 receptor antagonist to the mouse model also reduces 5-FU-induced intestinal mucositis [38].…”
Section: Discussionmentioning
confidence: 96%
“…Production of reactive oxygen and nitrogen species and oxidative stress are wellcharacterized upstream mediators of NF-κB activation as well as inflammasomes [51,52]. Oxygen radical scavengers and antioxidant enzymes, such as superoxide dismutase, have shown promise as anti-mucotoxic agents [53][54][55]. As such, there remains a clear benefit to targeting NF-κB-mediated inflammatory signaling, including upstream and downstream regulators, for prevention of oral and intestinal mucositis.…”
Section: Sophisticated Targeting Of Inflammationmentioning
confidence: 99%